The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1177/0890334414561264
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding among Adolescent Mothers

Abstract: Despite growing evidence of the benefits of breastfeeding, rates of breastfeeding remain disproportionately low among adolescent mothers compared with older mothers in the United States. Current interventions primarily target adult women, and little evidence is available for breastfeeding promotion among young women. Accordingly, we aim to review interventions designed to improve breastfeeding rates among adolescents to make recommendations for future research and practice. We searched MEDLINE and PsycINFO for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…Maternal grandmother support of breastfeeding showed a significant association with breastfeeding maintenance for at least 6 and 12 months, but not for 24 months, despite the magnitude of the association. This finding is not surprising, as receiving breastfeeding support from different sources – especially from the adolescent mother’s mother – is known to foster the practice [ 29 , 30 ]. A recent systematic review demonstrated that the opinion of the infant’s maternal grandmother regarding breastfeeding influences maternal decisions: when positive, it may increase by 12% the likelihood of the mother initiating breastfeeding; when negative, it may reduce by 70% the likelihood of breastfeeding [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal grandmother support of breastfeeding showed a significant association with breastfeeding maintenance for at least 6 and 12 months, but not for 24 months, despite the magnitude of the association. This finding is not surprising, as receiving breastfeeding support from different sources – especially from the adolescent mother’s mother – is known to foster the practice [ 29 , 30 ]. A recent systematic review demonstrated that the opinion of the infant’s maternal grandmother regarding breastfeeding influences maternal decisions: when positive, it may increase by 12% the likelihood of the mother initiating breastfeeding; when negative, it may reduce by 70% the likelihood of breastfeeding [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, records that teenage mothers provide less breast milk to their children in relation to the others, and also have more difficulties to initiate the practice of breastfeeding. 17 , 18 , 19 However, the studies do not refer to breastfeeding aspects among the teenagers assessed. It is possible that anatomical factors of the puerperal breasts of teenagers may lead to more vulnerability regarding the difficulties presented, but this aspect was not assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…the need for the adolescents to shift from their role as daughters to the role of mothers, the instability of their love relationships, financial and emotional dependence on the family, higher rates of postpartum depression [ 1 ], as well as distortions of self-image and self-esteem typical of this age range [ 22 ], the results reported for adult women can rarely be extrapolated to adolescent mothers. In a recent systematic review conducted to assess the effect of pro-breastfeeding interventions on the rates of breastfeeding in adolescent mothers from developed countries, Sipsma et al [ 23 ] pointed to the urgent need for more clinical trials designed to test new interventions targeted specifically at adolescent mothers. Moreover, those authors recommended the inclusion of the adolescent mothers’ mothers and partners in the interventions, a feature that was absent in the studies included in their review.…”
Section: Discussionmentioning
confidence: 99%